2021
DOI: 10.1002/admt.202100507
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insights on the Rheological Property of Polycaprolactone Composites with the Addition of Graphene

Abstract: Although polymer composites reinforced by graphene have been researched for almost two decades, the processing challenges caused by viscosity remains, especially for 3D printing. [3] Many experimental works have been conducted to assess the rheological properties of graphene reinforced composites, covering various factors such as weight/volume fraction, dispersion, surface modification, and shear rate. [4] However, the influence of the graphene size has not been systematically studied experimentally due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…MD simulations for PCL utilize the Optimized Potential for Liquid Simulation (OPLS) force field, 46 known for accurately reproducing PCL's mechanical and rheological properties compared to experimental data. 5,6 The initial configurations of CG models were directly mapped from the relaxed structures. Each CG model then undergoes relaxation using the same procedure as the full-atomic model, employing the corresponding potentials and thermostats, as detailed in the subsequent sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulations for PCL utilize the Optimized Potential for Liquid Simulation (OPLS) force field, 46 known for accurately reproducing PCL's mechanical and rheological properties compared to experimental data. 5,6 The initial configurations of CG models were directly mapped from the relaxed structures. Each CG model then undergoes relaxation using the same procedure as the full-atomic model, employing the corresponding potentials and thermostats, as detailed in the subsequent sections.…”
Section: Methodsmentioning
confidence: 99%
“…However, according to several recent research studies, the mechanical and rheological properties of polymer nanocomposites are influenced by the chain length dispersity 4 and the relative size of the polymer chains and nanofillers. [5][6][7] Thus, investigating the material properties of a large system with molecular structures has its significance in polymer physics and materials science.…”
Section: Introductionmentioning
confidence: 99%
“…The study of viscosity, complex viscosity, viscoelastic properties, creep & creep compliance of PCL composites are examined by researchers to analyze the effect of filler and its dispersion in PCL matrix. [10][11][12][13] There is still huge research gap available for rheological analysis of PCL copolymers, blends and composites to analyze molecular interaction. 14 Polydimethylsiloxane (PDMS) is an amorphous, biocompatible silicone polymer with low surface energy and excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation has been an effective method to study the solvation and gelation behaviors [ 14 , 15 ]. Cheng et al revealed that the formation and fracture of bridge hydrogen bonds caused by bubbling and CO 2 removal were the key factors leading to the CO 2 /N 2 switchable sol–gel transition behavior [ 16 ].…”
Section: Introductionmentioning
confidence: 99%